Pendidikan Karakter Perspektif Abdullah Nashih Ulwan dan Relevansinya dengan Teori Pendidikan Kontemporer - Farchan Nurhakim; Wasehudin Wasehudin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Character education is very important in this modern era, especially in creating children of the nation who have good attitudes. Therefore, the researcher wants to find out the extent of character education from Abdullah Nashih Ulwan's perspective and its relevance to contemporary educational theory. If we apply it in character education, according to Abdullah Nashih Ulwan, maybe I can apply it contemporary, adapted to the development of this contemporary education. The following are these articles: 1) Biography of Abdullah Nashih Ulwan, 2) Character education, 3) Purpose of character education, 4) Character education according to Abdullah Nasih Ulwan, and 5) Relevance of Abdullah Nashih Ulwan's thoughts on character education in contemporary education. This study uses a qualitative descriptive method to analyze the data that has been collected and uses an isometric analysis method. Examples of this type of data processing techniques are document creation, data processing, analysis, and the process of drawing conclusions. Character education is a deliberate attempt to help a person or student to understand and act on core ethical values ​​based on research results. The purpose of character education is a unique system for assessing a person's character based on the concept of composition, consciousness, or will, and is used to assess a person's character in the context of God Almighty. According to Abdullah Nashih Ulwan, a character school is also called a moral school. This requires the study of moral principles as well as attitudes and character. Abdullah Nashih Ulwan's relevance to contemporary higher education in terms of character education is moral and moral education.